Investment in New Renewable Energy: Contributions to the Economy, Environment, and National Resilience - Sundja, Ali; Mardiana, Dwi Atty; Sofilda, Eleonora; Hamzah, Muhammad Zilal (International Journal of Energy Economics and Policy, 2025)
Investment in renewable energy (RE) is significantly contributing to economic growth, environmental sustainability, and energy resilience. This economic growth is achieved by creating jobs, reducing greenhouse gas emissions, and decreasing dependence on fossil fuels. Despite the significant RE potential in Indonesia, challenges such as pollution, limited infrastructure, and price fluctuations still hinder national independence. Therefore, this study aimed to analyze the short-term and long-term relationships between renewable energy investment (REI) and economic growth, environmental sustainability, and resilience in Indonesia using the ARDL model and time series data from 2002 to 2022. Based on the analysis, the results showed that there was a significant cointegration relationship between the variables, suggesting the potential of REI to strengthen national resilience and support the transition to more sustainable energy. This study made an important contribution to understanding the dynamics of REI in Indonesia, providing policy recommendations to optimize economic and environmental benefits.